SEBUAH TINJAUAN SISTEMATIS: PENGARUH PENGGUNAAN KONDOM TERHADAP PROGRAM “DUA ANAK CUKUP” DI INDONESIA - Yusuf Hanafi Lubis; Susilawati Susilawati (Jurnal Kesehatan Masyarakat, 2022)
Government Regulation of the Republic of Indonesia Number 87 of 2014 concerning the development of occup-ation and Family Development, Family Planning, and Family Information System states that family planning (KB) programs are an effort to regulate the birth of children, distance and the ideal age of childbirth. The objectives of this study is to find out how much condom use in couples of childbearing age and strengthen the imple-mentation of the two-child program sufficiently in Indonesia. The research method used is to use systematic review by following the PRISMA checklist model in 2009 by search-ing the database with a publication period of 2018 - 2022 with keywords "condom use" and "two children enough". The results of the study are from 13 articles, there are 11 articles using cross sectional study designs and the rest usi-ng one group study, there are 9 articles that use chi square test data analysis, the rest use binary logistic test, wilcoxon test, rank spearman and t test. Conclusion is, the most dominant variable group of significance values seen from the score of α on condom use is behavior and service. Furthermore, insignificant influences were found on measurement variables, namely age, occupation, co-ntraceptive use (condoms), and peer influence.